Product Selection Decision Support System Insurance For Prospective Customers using AHP and TOPSIS: Product Selection Decision Support System Insurance For Prospective Customers using AHP and TOPSIS - Ridwan Baharudin; Septi Andryana; Sari Ningsih (Institute of Computer Science (IOCS), 2020)
In determining the insurance product common problems faced by insurance agents and prospective customers, namely the length of the process of determining customers' products and a lack of understanding of the products offered. It required a system that could be used by an insurance agent in the product selection process in accordance with the criteria of the prospective customer. This study aimed to design a decision support system for the selection of insurance products by using AHP and TOPSIS. The system is built to produce perangkingan insurance products according to the criteria of the prospective customer, ie, age, income, purpose, sex, smoking, and menika status. CMS system accuracy testing is done by comparing the output of the system by manual calculation process which is known there are differences in the results.